Study of the interrelation between the geneseses and reservoir properties of productive series deposits in Pirallahi field on the basis of oil-field geophysical data - К.А. Керімова; Н.Е. Алієв (Геофизический журнал, 2022)
Petrophysical properties of reservoir rocks are also influenced by a certain relationship between the lithological-mineralogical composition of rocks and the reservoir properties. For this reason, the study of the relationship between the genesis of Productive Series deposits and reservoir properties provides a basis for predicting the regularity of distribution of sand particles throughout the field and making some judgments about the development of porous and permeability zones. This, in turn, is of more scientific and practical importance while identifying variation of reservoir properties of rocks in sedimentary cover.